PENGARUH KURS DAN INFLASI TERHADAP PERDAGANGAN INTERNASIONAL DI SUMATERA BARAT TAHUN 1992-2022 - Hati, Melati Idaman; Devy, Tartila (LPPM - STIE SAKTI ALAM KERINCI, 2024)
During 1992–2022, West Sumatra's foreign commerce was likely significantly impacted by inflation and exchange rates. The purpose of this study is to analyze the impact of inflation and the currency rate on West Sumatra's foreign commerce from 1992 to 2022. Quantitative research using a descriptive approach is the strategy used in this study. statistics pertaining to West Sumatra's exchange rate, inflation, and international trade from 1992 to 2022, together with statistics from each semester, are utilized in this study. Next, the research uses the analytical tool method of Multiple Linear Regression with model tests (Autocorrelation Test, Multicollinearity Test, Normality Test, Heteroscedasticity Test) and hypothesis tests (Partial Test, Simultaneous Test, ?2) to draw conclusions. Macroeconomics and public economics provide the theoretical groundwork for analyses conducted using SPSS software. The research findings demonstrate that there is a considerable influence of Sig. 0.000 < α 0.05 of the exchange rate (X1) on international trade (Y). Next, we have the issue of inflation. The effect of (X2) on foreign trade (Y) is not statistically significant (Sig. 0.228 > α 0.05). At the same time, this research's independent factors significantly impact foreign commerce in West Sumatra from 1992 to 2022, as shown by Sig. 0.000 < α 0.05. With a coefficient of determination of 0.476, we may deduce that between 1992 and 2022, two variables the exchange rate (X1) and inflation (X2) contributed 47% to West Sumatra's international trade (Y), while other variables accounted for the other 52.4% .